Design of Level Sensor Prototype for Fuel Tank in Base Transceiver Station Facilities - Sufandi, Muhammad Ridhwan; Hadikusuma, Mohammad Ilyas; Saufa, Nanda Rusyda (ELKHA : Jurnal Teknik Elektro, 2024)
A monitoring system for fuel availability at Base Transceiver Stations (BTS) is an absolute necessity. The fuel availability in the generator set must be guaranteed because it ensures the energy supply and continuous operation. This research purpose is to create a robust and effective sensor that can be monitored in real-time so that industry players can estimate the consumption of fuel at the BTS in a certain period. The novelty of this research is that instead of looking at the amount of fuel consumption/reduction like the previous research, this study focuses on how much diesel availability is in the generator tank. So, calculating fuel requirements and predicting actual consumption are done directly. The sensor is a reed-switch oil level sensor and is connected to ESP32 as the microcontroller. It's installed horizontally and uses an optimum distance between sensors of 2.5 mm to improve the sensor reading's accuracy. The test results of converting voltage values into ADC signals on sensor readings produced a determination coefficient of 0.9987, which showed the reliability of the sensor-level design. The sensor precision test results produced an RSD value of 0.17% and the accuracy test produced an error range of -3% to 2% with an average error value of 1.59%. These results indicate that the designed level sensor has good precision and accuracy. Through this research, the provider can predict and plan their fuel consumption needs for BTS power supply and increase the Domestic Component Level in the sensor industry.